Faktor-faktor yang mempengaruhi profitabilitas pada Bank Umum Syariah - Rina, Rina; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2021)
The purpose of this study was to determine the effect of Financing To Deposit Ratio, Net Interest Margin, Corporate Social Responsibility, and Non-Performing Financing on Profitability in Islamic Commercial Bank. The sample used in this study was 12 banks with the sampling technique using purposive sampling. The analytical method used is multiple linear regression. The results show that the variable Financing To Deposit Ratio, Net Interest Margin has a positive effect on profitability. While Corporate Social Responsibility has no effect on profitability. Non-Performing Financing has a negative effect on profitability.